'Educated and educating as a Black woman' – an auto/biographical reflection on my grandmother's influence on my academic and professional outcomes. Issue 7 (3rd October 2021) - Owusu-Kwarteng, Louise
ABSTRACT: Adopting an auto/biographical approach, I discuss the impact my grandmother, Nana Elizabeth (Lizbet) Beyie had on the academic and career outcomes of myself and other female descendants. The paper begins with an exploration of Lizbet's biography and how she overcame struggles in terms of ensuring my mother's education in an era and context where female education was not prioritised. Following this, the paper moves to a focus on my continuation of Lizbet's legacy though my work in academia. I reflect on my career journey and positive and challenging experiences, as a Black female academic. I discuss the value of an auto/biographical approach to exploring these issues, since it enables reflections on the relationships between structural issues (e.g. racism/sexism; the education system; Ghanaian/British society) and personal experience/action as a result, not least our decision to help educate the next generations and allows for the voices of marginalised groups (including Black women) to be heard.